(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the study was to determine the prevalence and risk factors of bacterial urinary tract infection (UTI) in patients undergoing renal transplantation and to evaluate the possible bacterial agents that colonize the bladder in patients with or without micturition beforehand.Material and Methods: A total of 89 renal transplant patients were included in the study. Demographic characteristics of the patients such as age and gender, as well as the presence of micturition before transplantation, clinical findings, urine culture, and agents that showed growth were all retrospectively analyzed and the relevant data were recorded.Results: Of the total 89 patients, 17 (19.10%) developed a urinary tract infection within 12 months after transplantation. Eight of these patients required hospitalization for treatment, while four had at least two infection episodes. Escherichia coli and Klebsiella pneumonia were the two most common causative agents. A comparison of the groups with and without UTI revealed that micturition before transplantation was not a factor that affected the development of UTI (p > 0.05).Conclusion: Because UTI represents a severe problem for renal transplant patients, it must be evaluated in all patients. No correlation was found between preoperative micturition and postoperative UTI.